2014
DOI: 10.5714/cl.2014.15.1.050
|View full text |Cite
|
Sign up to set email alerts
|

Water and oxygen permeation through transparent ethylene vinyl alcohol/(graphene oxide) membranes

Abstract: We prepared ethylene vinyl alcohol (EVOH)/graphene oxide (GO) membranes by solution casting method. X-ray diffraction analysis showed that GOs were fully exfoliated in the EVOH/GO membrane. The glass transition temperatures of EVOH were increased by adding GOs into EVOH. The melting temperatures of EVOH/GO composites were decreased by adding GOs into EVOH, indicating that GOs may inhibit the crystallization of EVOH during non-isothermal crystallization. However, the equilibrium melting temperatures of EVOH wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 29 publications
0
12
0
2
Order By: Relevance
“…For cyclic olefin/graphene nanocomposites, a 6ºC increase in T g was measured [102] and for a study on PVOH/graphene oxide an increase of 6ºC was observed [94]. However, for another paper on PVOH/GO [112] there was no shift in T g and neither was any reported for EVOH/GO [99].…”
Section: Review Of Model Validationmentioning
confidence: 95%
See 2 more Smart Citations
“…For cyclic olefin/graphene nanocomposites, a 6ºC increase in T g was measured [102] and for a study on PVOH/graphene oxide an increase of 6ºC was observed [94]. However, for another paper on PVOH/GO [112] there was no shift in T g and neither was any reported for EVOH/GO [99].…”
Section: Review Of Model Validationmentioning
confidence: 95%
“…In another study [99], the aspect ratio was calculated to be 350 from the Nielsen model. at a low graphene oxide content of only 0.001 wt.%, and then gradually further decreased as the filler content increased to 0.01 wt.%, as shown in Figure 6.…”
Section: Water Barrier Properties Of Polymer/graphene Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the addition of GO also decreased the transparency to 84% at a wavelength of 550 nm. [80] Kim and Cha (2014) revealed that the incorporation of inorganic planar-structured nanoclay MMT can lead to a dramatic decrease of both P O 2 at 23 C, 50% RH and water vapor permeability (P H 2 O ) at 40 C 90% RH: at 3 wt% the decrease was most prominent, respectively 59.4 and 90.1%. There was also an improvement in transparency and mechanical properties.…”
Section: Additivesmentioning
confidence: 99%
“…Entre los polímeros más usados para este propósito tenemos el polímero termoplástico Etilen Vinil Alcohol (EVOH). El EVOH presenta una excelente resistencia química, así como una muy buena propiedad de barrera de gases como el oxígeno, solventes orgánicos y aromas de los alimentos, además de una muy buena transparencia [1][2][3].…”
Section: Introductionunclassified